Evaluation of damage characteristics of large LNG storage tanks under multiphase loading—An explosion occurs at high temperatures - Yanyan Li; Dayi Qian (Engineering Reports)
Abstract With the increasing demand and import of liquefied natural gas (LNG), large LNG receiving stations have been built one after another. LNG leakages can lead to fires or explosions in storage tanks. The coupling accident between explosion and fire is inevitable. In this paper, the selected K&C concrete constitutive model is simulated and verified by LS‐DYNA. Based on the verified material body model, it was applied to a large LNG storage tank. A two‐step analysis method (thermal analysis—impact analysis) was used to simulate the whole process of impact of different equivalent TNT on a large LNG storage tank at 800°C. The results show that under the combined action of high temperature and bidirectional load equivalent to 500 kg TNT, the center of the tank roof is damaged. Under the combined action of high temperature and two‐way load equivalent to 800 kg TNT, the entire tank roof was destroyed, and the maximum expansion deformation distance at the top of the tank reached 137.9 mm. The research results can provide theoretical reference for the safety design of storage tank under impact and high temperature, enhance the bearing capacity of outer tank and improve the safety of tank farm.